2023
DOI: 10.1111/bioe.13135
|View full text |Cite
|
Sign up to set email alerts
|

Is suffering a sufficient legitimation for UTx?

Abstract: Uterus transplantation is a relatively new intervention. A woman with absolute uterine factor infertility receives, by a surgical procedure, a transplanted uterus, most often by living donation. The uterus recipient may thus become pregnant and conceive her own child. As with any other medical treatment, UTx requires legitimation. The anticipated benefits must outweigh the risks of the medical intervention. The risks and benefits of UTx are by no means unequivocal and cannot be easily determined. The benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…In many countries, UTx is not covered by the public healthcare system: a recent study from Denmark [11] evaluated the estimated total costs for LD UTx at EUR 93850, including preoperative investigations, transplantation surgeries, 2-year followup with immunosuppressive therapy, and hysterectomy, and the authors concluded that the potential benefits of UTx do not justify the associated risks and costs of the procedure [11]. Moreover, some authors have argued that the existential suffering addressed by UTx does not possess a sufficiently strong normative value to legitimize such a high-risk and expensive procedure [70]. In this view, UTx may represent an inappropriate use of limited healthcare resources towards life-threatening conditions that should be prioritized over non-life-saving conditions such as UTx [71].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In many countries, UTx is not covered by the public healthcare system: a recent study from Denmark [11] evaluated the estimated total costs for LD UTx at EUR 93850, including preoperative investigations, transplantation surgeries, 2-year followup with immunosuppressive therapy, and hysterectomy, and the authors concluded that the potential benefits of UTx do not justify the associated risks and costs of the procedure [11]. Moreover, some authors have argued that the existential suffering addressed by UTx does not possess a sufficiently strong normative value to legitimize such a high-risk and expensive procedure [70]. In this view, UTx may represent an inappropriate use of limited healthcare resources towards life-threatening conditions that should be prioritized over non-life-saving conditions such as UTx [71].…”
Section: Future Perspectivesmentioning
confidence: 99%